NO MORE GRID GIRLS AT FORMULA ONE: THE DISCOURSE ANALYSIS ON HOSTESSES’ SEXUALIZED BODIES, OBJECTIFICATION, AND FEMALE AGENCY - Jakubowska, Honorata (Society Register, 2018)
At the beginning of 2018, Liberty Media, the owner of Formula One (hereafter, F1), decided to drop so-called grid girls from the race weekends beginning with the 2018 season, which has created an opportunity to analyze the perception of hostesses’ status and their bodies in contemporary sport. The discourse on the decision and the partial concessions in its enforcement is analyzed within the theoretical framework related to second and third waves of the feminist movement and the concepts of sexual objectification and agency. The results reveal that the grid girls’ presence is perceived both as unsuitable for modern times, values and #metoo culture climate and as “normal” and a “good tradition.” Additionally, the grid girls themselves accuse feminists of having caused them to lose their jobs, arguing that, although their positions are based on physical attractiveness and a sexualized body, it has been done by them voluntarily and with pleasure. The discourse on gird girls in F1 fits into the critical discourses on female (sexualized) body images in sport, but, on the other hand, it includes persons who have usually not been taken into account because of their auxiliary role in sports events.